Temperature Dependence of Chemical and Microbiological Chloramine Decay in Bulk Waters of Distribution System - Sathasivan, Arumugam; Chiang, Jacob; Nolan, P. (IWA Publishing, 2009)
Chloramine decays in distribution system due to wall and bulk water reactions. In bulk water, the decay could either be due to chemical or microbiological reactions. Without such distinction it is not possible to model chloramine decay in an actual distribution system since microbiological decay depends on different factors compared with chemical decay. The dependence of chloramine decay on chemical reactions is mostly understood. Although it is widely accepted that microbiological reactions could accelerate chloramine decay, quantification had not been possible until the microbiological decay factor method was proposed. In this paper, the effect of temperature on microbial and chemical decay coefficients is presented. This was done by following the procedure of the microbiological decay factor method but by varying the temperature of incubation between 18 and 30°C. The procedure was repeated for several samples. The results indicated that it is possible to express temperature dependence of both microbiological and chemical coefficients using the Arrhenius equation within the tested temperature range. Estimated E/R values were found to be 3,551±705 K-1 and 6,924±1,700 K-1 for chemical and microbiological decay rates respectively. Traditionally, it is believed that every 10°C rise would double the decay rate coefficients. However, the E/R value estimated in this study shows that a 16-17°C temperature rise is needed to double the chemical chloramine decay rate.A possible application to predict residuals in summer using winter water quality results is demonstrated. Results indicated that microbial decay factor method could help pre-warning water utilities of possible residual loss in summer. Traditional indicators could not offer such distinction.